Measurement of narcolepsy symptoms: The Narcolepsy Severity Scale. (4th April 2017) - Dauvilliers, Yves; Beziat, Severine; Pesenti, Carole; Lopez, Regis; Barateau, Lucie; Carlander, Bertrand; Luca, Gianina; Tafti, Mehdi; Morin, Charles M.; Billiard, Michel; Jaussent, Isabelle
Abstract : Objective: To validate the Narcolepsy Severity Scale (NSS), a brief clinical instrument to evaluate the severity and consequences of symptoms in patients with narcolepsy type 1 (NT1). Methods: A 15-item scale to assess the frequency and severity of excessive daytime sleepiness, cataplexy, hypnagogic hallucinations, sleep paralysis, and disrupted nighttime sleep was developed and validated by sleep experts with patients' feedback. Seventy untreated and 146 treated adult patients with NT1 were evaluated and completed the NSS in a single reference sleep center. The NSS psychometric properties, score changes with treatment, and convergent validity with other clinical parameters were assessed. Results: The NSS showed good psychometric properties with significant item-total score correlations. The factor analysis indicated a 3-factor solution with good reliability, expressed by satisfactory Cronbach α values. The NSS total score temporal stability was good. Significant NSS score differences were observed between untreated and treated patients (dependent sample, 41 patients before and after sleep therapy; independent sample, 29 drug-free and 105 treated patients). Scores were lower in the treated populations (10-point difference between groups), without ceiling effect. Significant correlations were found among NSS total score and daytime sleepiness (Epworth Sleepiness Scale, Mean Sleep Latency Test), depressive symptoms, and health-related quality of life. Conclusions: The NSS can be considered a reliable and valid clinical tool for the quantification of narcolepsy symptoms to monitor and optimize narcolepsy management.